Examining school culture in Flemish and Chinese primary schools. (July 2014) - Zhu, Chang; Devos, Geert; Tondeur, Jo
The aim of this research is to gain understanding about school culture characteristics of primary schools in the Flemish and Chinese context. The study was carried out in Flanders (Belgium) and China, involving a total of 44 Flemish schools and 40 Chinese schools. The School Culture Scales were used to measure five school culture dimensions with regard to goal orientation, leadership, innovation orientation, participative decision making and formal relationships. The School Culture Scales were validated in both contexts, and within-group agreement indexes were calculated. The results show that on average, the Flemish schools scored higher than the Chinese schools in four dimensions of the school culture features. Within-group differences were also found. The differences between and among the Chinese and Flemish schools are discussed.